Effect of soft-core pornography on female sexuality. Issue 2 (June 2016) - Abd El-Rahman, Sherine H.; Sanad, Eman M.; Bayomy, Hanaa H.
Abstract : Background: In the Arab world, consumption of soft-core pornography has increased in recent years. This type of pornography can motivate sexual behaviors that can affect health either positively or negatively. Objective: The aim of this study was to evaluate the effect of soft-core pornography on female sexuality and to assess its effect on female sexual desire, orgasm, and vaginal lubrication. Participants and methods: This is a cross-sectional study in which 200 sexually active married women were administered a self-filling questionnaire covering different aspects of female sexuality. All participants were free from any disease known to affect sexual function. Results: In total 52% of the participants and 59.5% of their husbands were positive watchers. An overall 51.6% of participants who were aware that their husbands were positive watchers reported experiencing negative emotions (depression, jealous), whereas 77% reported changes in their husbands' attitude. Negative watchers were more satisfied with their sexual life compared with their counterparts. Although watching soft-core pornography had a statistically significant effect on sexual desire, vaginal lubrication, ability to reach orgasm, and masturbation, it had no statistically significant effect on coital frequency. Conclusion: Watching soft-core pornography affects female sexual life by increasing sexual boredom in both men and women, causing relational difficulties.